Travelling Far and Wide? Applying the Multiple Streams Framework to Policy-Making in Autocracies - Nicole Herweg; Nikolaos Zahariadis; Reimut Zohlnhöfer (Politische Vierteljahresschrift, 2022)
The Multiple Streams Framework (MSF) builds on the concepts of timing and ambiguity and their effects on the policy process. Since its introduction to agenda-setting in the U.S. presidential system, scholars have transferred the MSF's core ideas to multiple issue areas, policy stages, and political systems. However, what has been lacking so far is a~thorough discussion of the MSF's travelling capacity to nondemocratic forms of government. Building on a~brief summary of the MSF's main ideas, this article discusses the challenges that policy-making in autocracies poses for MSF applications and ways to adapt it to the peculiarities that are typical for these regimes. The article focuses on the agenda-setting stage in which formal institutions are less important and introduces falsifiable hypotheses explaining agenda change. Due to tremendous differences regarding the organization of the decision-making process in autocratic regimes, the article only sketches out how the MSF could be adapted to explain policy change in this institutional setting. The article concludes with a~discussion of whether the MSF is stretched too far by applying it to nondemocratic systems. It turns out that in theoretical and conceptual terms, the MSF travels surprisingly well to these systems. – – Der Multiple-Streams-Ansatz (MSA) basiert auf den Konzepten Zeitknappheit und Ambiguität und ihrer Bedeutung für den politischen Prozess. Seit der MSA für die Analyse des Agenda-Settings in den USA entwickelt wurde, sind seine Kerninhalte auf eine Vielzahl von Politikfeldern, Phasen des Policy-Zyklus und politische Systeme übertragen worden. Was bislang allerdings noch weitgehend fehlt, ist eine Diskussion der Frage, inwieweit der Ansatz sich auch auf Nichtdemokratien übertragen lässt. Nach einer kurzen Zusammenfassung des MSA diskutiert dieser Aufsatz die Herausforderungen einer Übertragung des Ansatzes auf Autokratien und präsentiert Möglichkeiten, ihn an die Besonderheiten dieser politischen Systeme anzupassen. Wir konzentrieren uns auf die Agenda-Setting-Phase, in der formale Institutionen eine geringere Rolle spielen, und schlagen falsifizierbare Hypothesen vor, mit denen Agendawandel erklärt werden kann. Aufgrund der größeren Varianz hinsichtlich der Institutionen der Entscheidungsfindung in Autokratien skizzieren wir dagegen lediglich, wie der MSA auch Politikwandel in Nichtdemokratien erklären könnte. Abschließend diskutieren wir, ob der MSA bei der Anwendung auf Autokratien zu weit gedehnt wird. Tatsächlich finden wir aber, dass er sich zumindest auf der theoretischen und konzeptionellen Ebene erstaunlich gut auf solche politischen Systeme übertragen lässt.
Keywords: 320; Agenda-setting; Decision-making; Problem definition; Nondemocratic regimes; Policy change; Entscheidungsfindung; Multiple-Streams-Ansatz; Problemdefinition; Politikwandel